2019
DOI: 10.3126/jpan.v8i1.26336
|View full text |Cite
|
Sign up to set email alerts
|

Addiction psychiatry training experience, belief about addiction and brief screening for substance use among medical interns: A cross-sectional survey

Abstract: Introduction: Substance use and Substance Use Disorders (SUDs) have been shown to contribute substantially to the global burden of disease. However health workers belief system and attitude towards understanding and conceptualizing addiction makes the difference in the approach and treatment of the condition. This study tries to focus on the understanding and belief system of medical interns, and to see and contrast if their use of substance and their training about addiction during MBBS makes any difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Their belief system of addiction of substance (tobacco, alcohol, cannabis, heroin and other substance) assessed with Addiction Belief Scale showed majority of medical students believing predominantly the biological model of illness. 61 A study among Sadhus revealed that only 14% believed Lord Shiva to promote its use. Less educated and Naga sect Sadhus were more likely to view cannabis as a boon of Lord Shiva and provide it to devotees.…”
Section: Knowledge Attitude and Practice Study About Cannabismentioning
confidence: 99%
“…Their belief system of addiction of substance (tobacco, alcohol, cannabis, heroin and other substance) assessed with Addiction Belief Scale showed majority of medical students believing predominantly the biological model of illness. 61 A study among Sadhus revealed that only 14% believed Lord Shiva to promote its use. Less educated and Naga sect Sadhus were more likely to view cannabis as a boon of Lord Shiva and provide it to devotees.…”
Section: Knowledge Attitude and Practice Study About Cannabismentioning
confidence: 99%